The Impact of Cutting Tool Materials on Cutting Force - ahmad kamely, mohamad; mohd yusuf, noordin (WASET, 2011)
A judicious choice of insert material, tool geometry and cutting conditions can make hard turning produce better surfaces than grinding. In the present study, an attempt has been made to investigate the effect of cutting tool materials on cutting forces (feed force, thrust force and cutting force) in finish hard turning of AISI D2 cold work tool steel. In conclusion of the results obtained with a constant depth of cut and feed rate, it is important to note that cutting force is directly affected by cutting tool material.